2018
DOI: 10.1007/s11060-018-2766-z
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of a synthetic epsin mimetic peptide in glioma tumor model: uncovering multiple mechanisms beyond the VEGF-associated tumor angiogenesis

Abstract: Binding of epsin ubiquitin-interacting motif (UIM) with ubiquitylated VEGFR2 is a critical mechanism for epsin-dependent VEGFR2 endocytosis and physiological angiogenesis. Deletion of epsins in vessel endothelium produces uncontrolled tumor angiogenesis and retards tumor growth in animal models. The aim of this study is to test the therapeutic efficacy and targeting specificity of a chemically-synthesized peptide, UPI, which compete for epsin binding sites in VEGFR2 and potentially inhibits Epsin-VEGFR2 intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…To be able to selectively modify the trafficking of disease-relevant surface proteins will for example open up new avenues for targeted cancer therapies. A prominent example is the use of peptides blocking the Epsin-VEGFR2 interaction to impair tumor angiogenesis which inhibits tumor growth and metastasis in mouse models [332][333][334]. The selective inhibition of endocytosis could also prove useful in combination with cancer therapies, which exploit the antibody-based recognition of surface-localized tumor markers such as EGFR for the delivery of cytotoxic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…To be able to selectively modify the trafficking of disease-relevant surface proteins will for example open up new avenues for targeted cancer therapies. A prominent example is the use of peptides blocking the Epsin-VEGFR2 interaction to impair tumor angiogenesis which inhibits tumor growth and metastasis in mouse models [332][333][334]. The selective inhibition of endocytosis could also prove useful in combination with cancer therapies, which exploit the antibody-based recognition of surface-localized tumor markers such as EGFR for the delivery of cytotoxic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] A study revealed that a variety of mechanisms are found beyond the VEGF-related angiogenesis of tumors. [ 10 ] Hypoxia is one of the most important regulatory factors for the expression of VEGF. In the present study, RT-qPCR results revealed that the mRNA expression levels of Cyr61, CTGF, and VEGF in muscle tissues were higher in the PM and DM groups than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…2017; Dong et al, 2018). More recent studies showed that epsins are involved in regulating Notch signaling to modulate murine embryonic stem cells exit from pluripotency (Cardano et al, 2019).…”
Section: Epsin-deficient Animal Modelsmentioning
confidence: 99%